Borrelia burgdorferi swims with a planar waveform similar to that of eukaryotic flagella. - Goldstein, S F (1994)
Borrelia burgdorferi is a motile spirochete with multiple internal periplasmic flagella (PFs) attached near each end of the cell cylinder; these PFs overlap in the cell center. We analyzed the shape and motion of wild type and PF-deficient mutants using both photomicrography and video microscopy. We found that swimming cells resembled the dynamic movements of eukaryotic flagella. In contrast to helically shaped spirochetes, which propagate spiral waves, translating B. burgdorferi swam with a planar waveform with occasional axial twists; waves had a peak-to-peak amplitude of 0.85 micron and a wavelength of 3.19 microns. Planar waves began full-sized at the anterior end and propagated toward the back end of the cell. Concomitantly, these waves gyrated counter-clockwise as viewed from the posterior end along the cell axis. In nontranslating cells, wave propagation ceased. Either the waveform of nontranslating cells resembled the translating form, or the cells became markedly contorted. Cells of the PF-deficient mutant isolated by Sadziene et al. [Sadziene, A., Thomas, D. D., Bundoc, V. G., Holt, S. C. & Barbour, A. G. (1991) J. Clin. Invest. 88, 82-92] were found to be relatively straight. The results suggest that the shape of B. burgdorferi is dictated by interactions between the cell body and the PFs. In addition, the PFs from opposite ends of the cell are believed to interact with one another so that during the markedly distorted nontranslational form, the PFs from opposite ends rotate in opposing directions around one another, causing the cell to bend.